Solomon and the Queen of Sheba: Historical and Theological Issues in the First Book of Kings and in the Paintings of Piero della Francesca - Emanuelle Pastore; Laura de Fuccia Lederer (Religions, 2025)
The first book of Kings succinctly evokes—in only thirteen verses—the mysterious figure of a queen who came from the distant land of Sheba to test Solomon’s wisdom (1 Kgs 10.1–13). Who would have predicted that this modest episode celebrating the glory of the ancient kings of Jerusalem would be so popular? The episode has spread far beyond the boundaries of the two Testaments, notably in painting. Piero della Francesca’s fresco cycle in Arezzo is a fine example in this respect. Inspired by the Golden Legend, the Florentine painter recreates the scenes of the discovery of the true Cross. Solomon and the Queen of Sheba meet against the backdrop of the fall of Constantinople in 1453. Whether intra- or extra-biblical, ancient or modern, rereading of the original episode reveals issues that are as much historical as they are theological.